Karakteristik fisik dan daya terima biskuit dengan penambahan tepung porang dan tepung jagung sebagai pangan darurat - Rahma Bayunita Hapsari; Gusti Ananda Syahputri; Kania Uswama (AGROINTEK, 2025)
In an emergency such as a natural disaster, one type of special food is needed, namely Emergency Food Products (EFP). One of these ready-to-eat foods is biscuits. The purpose of this study was to determine the physical characteristics and acceptability of biscuits with the addition of porang flour and corn flour as emergency food. This study design used a Completely Randomized Design (CRD) using two factors, namely the porang flour and corn flour formulation factor and the pre-treatment temperature factor (-18oC and 4oC). The analysis used was texture analysis including crispiness and fracturability, color analysis and sensory analysis including taste, color, and aroma. The results showed that the porang flour and corn flour formulation factors had a significant effect on the physical characteristics in the form of crispiness, fracturability, color, and acceptability. While the pre-treatment temperature factor only had a significant effect on the hardness of the biscuits. So based on the characteristics above, the F2D1 sample with a ratio of 65 g porang flour: 50 g corn flour and a pre-treatment temperature of -18oC is the best sample and is suitable as emergency food.